Achieving performance and longevity with butane-operated low-temperature solid oxide fuel cells using low-cost Cu and CeO2 catalysts. Issue 5 (9th November 2021) - Thieu, Cam-Anh; Yang, Sungeun; Ji, Ho-Il; Kim, Hyoungchul; Yoon, Kyung Joong; Lee, Jong-Ho; Son, Ji-Won
Abstract : Record high performance and longevity is reported for a butane-fueled low-temperature-operating solid oxide fuel cell (LT-SOFC). Affordable catalysts, Cu and CeO2, were incorporated into a thin-film-based SOFC to enable this remarkable enhancement. Abstract : The use of thin-film solid oxide fuel cells (TF-SOFCs) can effectively lower the operating temperature of a typical solid oxide fuel cell (SOFC) below 600 °C, while maintaining high efficiency and using low-cost catalysts. However, the fuel flexibility in SOFCs becomes a significant challenge at lower operating temperatures, resulting in the need for expensive noble-metal catalysts. The effective implementation of low-cost catalysts, Cu and CeO2, in a TF-SOFC presents a solution to this problem. Cu is inserted directly near the electrolyte–anode interface via a combination of pulsed laser deposition and sputtering to assist the electrochemical reactions, and the anode support, which constitutes the main volume of the cell, is infiltrated with CeO2 to effectively facilitate thermochemical reforming reactions. A comprehensive study of catalyst-modified cells (Cu–Ce-cell, Ce-cell, and Cu-cell) and a Ni/YSZ reference cell (ref-cell) is performed over n -butane fuel in an operating temperature range of 500 to 600 °C. The cell incorporating Cu and CeO2 (Cu–Ce-cell) shows a record high performance for a hydrocarbon-fueled SOFC, with a peak power density of 1120 mW cm −2 at 600 °C. Cu and CeO2 improve the activity of the steam reforming reaction, and CeO2 expands the triple-phase boundary, increasing the electrochemical activity. Cu–Ce-cell also degrades at a much slower rate than ref-cell. Post-reaction analysis proves that the drastic improvement in longevity is achieved as a result of the enhanced carbon deposition resistance of Cu–Ce-cell.